ICONOGRAPHY OF SOME CULT-IMAGES AND PAINTINGS OF SRI JAGANNATHA TEMPLE OF PURI IN ODISHA - Mohapatra, Ratnakar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of paper is to emphasize the iconography of some cult-images and paintings of Sri Jagannatha temple of Puri in Odisha. The artistic designs of the cult images of Sri Jagannatha temple is a significant facet of the Odishan sculptural art. After complete deplastering of Sri Jagannath temple in 1980’s, the detailed description of the sculptures of the vimana or main deula could be made possible to identify by scholars as well as visitors. The deplastered surface of the main deula (vimana) of Jagannatha temple has brought to light an array of sculptures. The iconography of cult-images of the Sri Jagannatha temple of Puri constitutes the predominating class among the sculptural arts of Odishan temples. Sri Jagannatha temple of Puri is adorned with excellent sculptures of cult images and the non-ionic figures & decorative motifs. The cult images of different sects like Vaishnavism, Buddhism, Jainism, etc. are found depicted in the Sri Jagannatha temple of Puri, which are very important in historical prospective. Wooden images of “Jagannatha Trinity” of Puri are the best wooden craftsmanship of Odishan artists/sculptors of Eastern India. The side deities of the main deula possess the features of the Ganga art of Odisha. The sculptures depicting the worship of Durga, Madhava (Jagannatha) and Sivalinga by the king is finely inserted in the outer bada wall niche of the bhogamandapa of Sri Jagannatha temple. This is very significance and it symbolise the composite of Sakta-Vaishnava and Saiva religions of the Hindu pantheon in the sacred place of Lord Jagannatha of Puri. The walls and ceiling of the jagamohana as well as the nathamandapa of Sri Jagannatha temple are beautifully illustrated with paintings of Hindu gods and goddesses. The sculptural art of some cult-images and available paintings of Sri Jagannatha temple of Puri are incredibly importance from the artistic point of view. Hence, the present article is concerned with the sculptural features of some cult images along with paintings of the temple of Sri Jagannatha of Puri in Odisha.